Appraisal and evaluation of the instruments measuring the nursing work environment: A systematic review. (28th February 2022) - Chang, Yu‐Chun; Chang, Hsin‐Yi; Feng, Jui‐Ying
Abstract: Aims: To appraise the current instruments available for measuring the nursing work environment and re‐examine the definition and construct of the nursing work environment. Background: A psychometrically sound instrument is fundamental to understanding and improving the nursing work environment. The nursing work environment is a complex construct, and its definition remains inconclusive. None of the instruments available is considered as the gold standard. Evaluation: A comprehensive searching was undertaken in August 2021 in six databases according to PRISMA. The COSMIN and modified GRADE were applied to assess the methodological quality and measurement properties of the instruments. Instruments were categorized into three levels. The definition and construct of nursing work environment were revisited. Key issues: Forty‐one studies (19 instruments) were included. One, fourteen, and four instruments are respectively appraised as A‐, B‐ and C‐level recommendation. Definition and eight labels of nursing work environment are identified. Conclusion: This paper provides recommendations for selecting a proper instrument for the nursing work environment. Implications for nursing management: This study helps nurse managers to select instruments and understand the construct of the nursing work environment. The eight labels can be used as a reference for tailoring policy aimed at creating a favourable nursing work environment.